2008
DOI: 10.1093/carcin/bgn228
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell-derived factor-1α (SDF-1α/CXCL12)-enhanced angiogenesis of human basal cell carcinoma cells involves ERK1/2–NF-κB/interleukin-6 pathway

Abstract: Stromal cell-derived factor 1alpha (SDF-1alpha) (CXCL12) has been observed to enhance tumor angiogenesis. However, the comprehensive role of SDF-1alpha (CXCL12)-CXCR4 interaction, exerted during angiogenesis, has not been well understood. We have previously demonstrated that human basal cell carcinoma (BCC) tissues and a BCC cell line (BCC-1/KMC) had significant expression of CXCR4, whose level was higher in invasive than in the non-invasive BCC types. Here, we observed that human BCC tissues with high express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 42 publications
1
32
1
Order By: Relevance
“…These findings complement those of previous studies showing that tumor-derived CXCL12 stimulates angiogenesis in other human cancers. 24,50,51 However, in the context of MM, our data directly contradict findings published by Menu et al, 11 who showed that the administration of T140 had no effect on bone marrow microvessel density in myelomatous 5T33MM mice. This may, in part, be explained by the fact that 5T33MM cells do not express CXCL12 and as such, the ability of 5T33MM-derived CXCL12 to stimulate angiogenesis was not under direct investigation.…”
Section: Discussioncontrasting
confidence: 56%
“…These findings complement those of previous studies showing that tumor-derived CXCL12 stimulates angiogenesis in other human cancers. 24,50,51 However, in the context of MM, our data directly contradict findings published by Menu et al, 11 who showed that the administration of T140 had no effect on bone marrow microvessel density in myelomatous 5T33MM mice. This may, in part, be explained by the fact that 5T33MM cells do not express CXCL12 and as such, the ability of 5T33MM-derived CXCL12 to stimulate angiogenesis was not under direct investigation.…”
Section: Discussioncontrasting
confidence: 56%
“…Very recently, it has been shown that RAF inhibitors prime cells with wild-type RAF to activate the mitogen-activated protein kinase pathway [20,21]. This pathway plays a role in the pathogenesis of SCC of the skin [22], but potentially also in BCC [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-6 triggered the migration of endothelial cells when added to NAFs, whereas TNFα inhibited the migration when added to CAFs, suggesting that these factors secreted by stromal fibroblasts were responsible for the observed effects. The up-regulation of IL-6 and the involvement of the IL-6 pathway by the p50 subunit of nuclear factor-κB or the involvement of the IL-6 pathway trough SDF-1A (CXCL12) in the progress of angiogenesis was recently shown (59,60). There could be a direct effect of IL-6 on the enhanced migration of endothelial cells via up-regulation of angiogenic relevant factors in the endothelial cells.…”
Section: Discussionmentioning
confidence: 99%